Meridional Flow in the Solar Polar Caps Revealed by Magnetic Field Observation and Simulation - Yang, Shuhong; Jiang, Jie; Wang, Zifan; Hou, Yijun; Jin, Chunlan; Song, Qiao; Luo, Yukun; Li, Ting; Zhang, Jun; Zhang, Yuzong; Zhou, Guiping; Deng, Yuanyong; et al. (The Astrophysical journal, 2024)
As a large-scale motion on the Sun, the meridional flow plays an important role in determining magnetic structure and strength and solar cycle. However, the meridional flow near the solar poles is still unclear. The Hinode observations show that the magnetic flux density in polar caps decreases from the lower latitudes to the poles. Using a surface flux transport model, we simulate the global radial magnetic field to explore the physical process leading to the observed polar magnetic distribution pattern. For the first time, the high-resolution observations of the polar magnetic fields observed by Hinode are used to directly constrain the simulation. Our simulation reproduces the observed properties of the polar magnetic fields, suggesting the existence of a counter-cell meridional flow in the solar polar caps with a maximum amplitude of about 3 m s −1 .